2011
DOI: 10.1111/j.1610-0387.2011.07657.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Monitoring of epidermal absorption of hazardous substances by confocal Raman micro‐spectroscopy

Abstract: CRS has the potential to provide fast, accurate and reliable results for advanced studies of in vivo percutaneous absorption kinetics of hazardous substances in human skin. This will require further research with other substances and under differing conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…By employing this method, a semi‐quantitative analysis of skin barrier components can be performed, for example SC lipids, natural moisturizing factors. CRS has emerged for high spatial and temporal resolution evaluation of SC barrier function and hydration . The combination of a confocal signal acquisition with inelastic (Raman) photon scattering permits the direct determination of the SC molecular composition and distribution.…”
Section: Introductionmentioning
confidence: 99%
“…By employing this method, a semi‐quantitative analysis of skin barrier components can be performed, for example SC lipids, natural moisturizing factors. CRS has emerged for high spatial and temporal resolution evaluation of SC barrier function and hydration . The combination of a confocal signal acquisition with inelastic (Raman) photon scattering permits the direct determination of the SC molecular composition and distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that only the 3 first mixtures (up to glycerol: water, 20:80) penetrated the SC entirely. Moreover, it has been shown that 2‐butoxyethanol penetrates the skin markedly faster when dissolved in water as compared with ethanol . Thus, as the present used compound were pure chemicals, their diffusions appeared to be lower.…”
Section: Resultsmentioning
confidence: 81%
“…This is especially important for those products which are designed for use around the oral or genital mucosa. In a variety of products such as these, mineral oils, petrolatum, and waxes are used due to their excellent skin tolerance, and skin protecting properties . Depending on the product type, the mineral oil content may vary from low to up to nearly 100% and is often supported with presence of both petrolatum and paraffin waxes.…”
Section: Introductionmentioning
confidence: 99%
“…In a variety of products such as these, mineral oils, petrolatum, and waxes are used due to their excellent skin tolerance, and skin protecting properties. 15,16 Depending on the product type, the mineral oil content may vary from low to up to nearly 100% and is often supported with presence of both petrolatum and paraffin waxes. In products such as these toxicological considerations are important given that chemically, mineral oils, and (paraffin) waxes are mixtures of predominantly saturated hydrocarbons consisting of straight-chain, branched and ring structures with carbon chain lengths primarily greater than C16.…”
Section: Introductionmentioning
confidence: 99%